Mempelajari Biaya Perawatan Kendaraan Besar pada PT Buah Lestari Putra - Ajeng Zaizah Almahira; Candra Galang Gemilang Putra; Wahyudin Wahyudin (Jurnal Ilmiah Wahana Pendidikan, 2022)
Along with increasing development in all fields, especially in the economic field, transportation facilities as one of the economic links are also experiencing rapid progress. Transportation services are one form of service that is needed by the community, both from the general public, government and industrial companies. PT. Sustainable fruit is a company that was initially engaged in the export and import of various kinds of fruit, but over time the company began to develop into the transportation sector. Engaged in transportation services PT. Buah Lestari rents out various types of vehicles such as trucks and buses. Companies engaged in transportation must pay attention to the cost of maintenance and what spare-pats are used in maintenance and the benefits of regular maintenance. At PT Buah Lestari Putra there are 123 types of spare-pats that must be replaced within the last 3 months and the cost is Rp. 52,212,000. Periodic maintenance also has many benefits such as, reducing the cost of a larger exit, more secure security, reducing downtime, etc.